2001
DOI: 10.1095/biolreprod64.5.1392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Estrous Cycle, Pregnancy, and Interferon Tau on 2′,5′-Oligoadenylate Synthetase Expression in the Ovine Uterus1

Abstract: The enzymes which comprise the 2',5'-oligoadenylate synthetase (OAS) family are interferon (IFN) stimulated genes which regulate ribonuclease L antiviral responses and may play additional roles in control of cellular growth and differentiation. This study characterized OAS expression in the endometrium of cyclic and pregnant ewes as well as determined effects of IFNtau and progesterone on OAS expression in cyclic or ovariectomized ewes and in endometrial epithelial and stromal cell lines. In cyclic ewes, low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 44 publications
(75 reference statements)
6
57
0
1
Order By: Relevance
“…Thus, OAS interaction with the PRL-R enhances PRL-mediated differentiated functions. Consistent with this observation, IFN-inducible OAS expression is correlated with increased Stat5-mediated differentiated functions in the pregnant ovine endometrium (Johnson et al, 2001). resulting in transcriptional activation of genes.…”
Section: Prl-r-interacting Proteinssupporting
confidence: 69%
“…Thus, OAS interaction with the PRL-R enhances PRL-mediated differentiated functions. Consistent with this observation, IFN-inducible OAS expression is correlated with increased Stat5-mediated differentiated functions in the pregnant ovine endometrium (Johnson et al, 2001). resulting in transcriptional activation of genes.…”
Section: Prl-r-interacting Proteinssupporting
confidence: 69%
“…This study revealed that expression of enJSRV-Env mRNA by conceptus trophectoderm decreases between Days 13 and 16 of a normal pregnancy. This decline of enJSRV mRNA could result from active processing through recruitment and activation of antiviral ISGs such as Mx or 2 0 ,5 0 -oligoadenylate synthetase (OAS), which are known to be induced by IFNT (Johnson et al 2001. On the other hand, enJSRV-Env mRNA may accumulate under the influence of a regulatory feedback controlled by secretions from BNCs, which would account for the decline in enJSRV-Env mRNA around Day 16 as numbers of BNC increase.…”
Section: Discussionmentioning
confidence: 99%
“…Esses complexos se ligam a regiões definidas no DNA chamadas de elementos responsivos à estimulação por interferons (ISREs) que regulam a expressão de ISGs (HANSEN et al, 1999). Dentre os ISGs que aumentam sua expressão durante o início da gestação em resposta ao IFNT, estão o 2',5' oligoadenilato sintetase (OAS; MIRANDO et al, 1991;SCHMITT et al, 1993;JOHNSON et al, 2001), o gene de resistência ao myxovirus 1 (MX1; (OTT et al, 1998) e o gene estimulado pelo interferon 15 (ISG15; NAIVAR et al, 1995;AUSTIN et al, 1996;JOHNSON et al, 1999). Estudos recentes demonstraram a expressão de ISGs em células do sangue (YANKEY et al, 2001;HAN et al, 2006;GIFFORD et al, 2007) e CL (OLIVEIRA et al, 2008;BOTT et al, 2010) logo após a sinalização por IFNT no início da gestação em ruminantes.…”
Section: Receptores De Prostaglandinasunclassified